Estimated phyllochron in low tunnel cultivated strawberry cultivars - Cocco,Kassia Luiza Teixeira (2016)
ABSTRACT: The aim of this study was to determine phyllochron in strawberry cultivars, from two origins during two crop years, conducted in low tunnel. Experiments were conducted at the Universidade Federal de Santa Maria, campus Frederico Westphalen (CESNORS/UFSM), Brazil, evaluating 'Camarosa', 'Camino Real' and 'Albion' strawberry cultivars. During the 2012 crop year, seedlings from Chile and Pelotas/RS, Brazil were evaluated, for the 2013 crop year, only seedlings from Chile were submitted to evaluations. In order to determine the phyllochron, twice a week the numbers of leaves (NL) of the main crown were counted and a regression between NL and accumulated thermal time (ATT) was held. The experimental design was a complete randomized block, with three repetitions with the evaluation of 12 plants per experimental unity, consisting of a factorial. For 2012 and 2013 crop years, it is possible to conclude that 'Camarosa' and 'Camino Real' cultivars required higher accumulation of degree-days (ºC day-1) to issue each successive leaf than cv. 'Albion', which, in turn, presented higher rates of leaf emergence, being considered earlier. Regarding to origin, seedlings from cv. 'Albion' from Chile presented lower total phyllochron values and for samples from Pelotas, no difference among cultivars was observed.